Color-tunable single-fluorophore supramolecular system with assembly-encoded emission - Wang, Qian; Zhang, Qi; Zhang, Qi-Wei; Li, Xin; Zhao, Cai-Xin; Xu, Tian-Yi; Qu, Da-Hui; Tian, He (Nature communications, 2020)
Regulating the fluorescent properties of organic small molecules in a controlled and dynamic manner has been a fundamental research goal. Although several strategies have been exploited, realizing multi-color molecular emission from a single fluorophore remains challenging. Herein, we demonstrate an emissive system by combining pyrene fluorophore and acylhydrazone units, which can generate multi-color switchable fluorescent emissions at different assembled states. Two kinds of supramolecular tools, amphiphilic self-assembly and γ-cyclodextrin mediated host-guest recognition, are used to manipulate the intermolecular aromatic stacking distances, resulting in the tunable fluorescent emission ranging from blue to yellow, including a pure white-light emission. Moreover, an external chemical signal, amylase, is introduced to control the assembly states of the system on a time scale, generating a distinct dynamic emission system. The dynamic properties of this multi-color fluorescent system can be also enabled in a hydrogel network, exhibiting a promising potential for intelligent fluorescent materials. Regulating fluorescent properties of small molecules in a controlled manner has been a fundamental research goal but realizing multi-color emission from a single fluorophore remains challenging. Here the authros demonstrate that combined pyrene fluorophore and acylhydrazone units show multi-color switchable fluorescent at different assembled states.